Importance of English in Engineering for Professional Communication: A Study in the Nepalese Context - Shrestha, Rup Narayan; Pahari, Bharat Raj; Awasthi, Jai Raj (Journal of the Institute of Engineering, 2017)
This article attempts to highlight the importance of English in the professional communication in the field of engineering in Nepal. The main objective of the article is to shed light on the role English language plays in the communication related to engineering. Based primarily on the review of some relevant literature available, the present article reveals the fact that English being one of the global languages used in a wide range of communicative fields all over the world, it serves as an important tool for professional communication in engineering in Nepal. Journal of the Institute of Engineering, 2016, 12(1): 222-227